2022-RA-642-ESGO Long term follow-up in patients treated with electrochemotherapy for vulvar cancer. (20th October 2022) - Perrone, Anna Myriam; Corrado, Giacomo; Garganese, Giorgia; Coada, Camelia Alexandra; Ferioli, Martina; de Crescenzo, Eugenia; Tesei, Marco; Dondi, Giulia; Tagliaferri, Luca; Stanislao, Marco Di; Fragomeni, Simona Maria; de Terlizzi, Francesca; et al.
Abstract : Introduction/Background: Recurrence of vulvar cancer (VC) poses management problems due to the advanced age and comorbidities of the patients. Electrochemotherapy (ECT) with bleomycin is a new treatment option for these cases. We previously evaluated the ECT short-term response of recurrent VCs refractory to standard therapies. To date, no long-term follow-up results are available in such patients. This is a multicenter observational study carried out in two Italian centers with the purpose of evaluating the two-year outcomes of these patients. Methodology: Data about patients, tumor characteristics, ECT cycles, clinical response and follow-up were recorded. The procedures were performed according to European Standard Operative Procedure (ESOPE) guidelines. Response was evaluated according to the RECIST criteria. Results: Fifty-one patients, with a median age of 81.1±7.9 years and affected by squamous cellular carcinoma were treated with ECT. The majority of patients received one ECT with a range between 1–4 sessions. No serious adverse events were reported. A total of 20 patients had complete remission (CR) among which 32% retained their disease-free status after 2-years (median recurrence time of 16.8 months). Out of the 13 patients with initial partial response (PR), 30% did not show disease progression (median recurrence time of 15.4 months). On the other hand, patients with stable (SD) or progressive disease (PD) showed signs of worsening after 3.9 and 5.3 months, respectively (p=0.04). As far as survival is concerned, median survival was 18.8 months for patients with CR, 13.1 months for patients with PR, 6.7 and 11.1 months for patients with SD and PD respectively (p=0.002). Conclusion: Long follow-up of VC patients has showed that those who benefit most from ECT treatment were complete responders. Based on these results and considering the scarce availability of treatment options for VC recurrences, ECT represents a promising alternative of these patients.